PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KEMAMPUAN BERTANYA SISWA KELAS VIII SMP MATERI CAHAYA DAN ALAT OPTIK - Safitri, Iin; Purnomo, Aris Rudi (Program Studi S1 Pendidikan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This research aimed at improving the questioning skills of junior high school students in guided inquiry learning in light and optical devices. This study uses a type of research, namely quantitative descriptive. The data analysis technique used is the n-gain test, the data collection technique uses a questionnaire (questionnaire) and tests. This research involved 30 students from class VIII-C of SMP and 1 science teacher. The results showed that all students already had moderate learning abilities with indicators of ability to ask questions. Therefore, it can be concluded that the high ability to ask students has an effect on science learning outcomes. (1) Students' ability to ask questions can be seen from the average pretest and posttest scores that have increased from 49% to 92% with a maximum score of 75. (2) the implementation of learning to obtain mode percentage> 3. (3) The response questionnaire obtained an average of 95% with a very good category.